WAKAF 100 MUSHAF AL-QUR'AN BERSAMA YATIM MANDIRI DI DESA PANGAWINAN - Hanifa, Millata; Muttaqin, Royhan Imamul; Tuhriyati, Tuhriyati (MIMBAR INTEGRITAS : Jurnal Pengabdian, 2025)
The best human being in Islam is the one who is most useful to others. The lack of Qur'an literacy in Indonesia in the aspect of not having Al-Qur'an mushaf at 11.3%, it is necessary to hold a real action activity to provide Qur'anic waqf directly to village communities in Indonesia. The 100 Mushaf Al-Qur'an waqf activity in pangawinan village was carried out with a participatory action approach in collaboration with Yatim Mandiri Serang Banten in particular, community leaders, youth and campus. This activity provides output results in the form of 100 Al-Qur'an mushaf and Al-Qur'an learning assistance services. The activity has a positive impact on the village of Pangawinan in the ability of Al-Qur'an literacy, both regarding the ownership of Al-Qur'an mushaf and the improvement of Al-Qur'an reading methods in tahsin and tajwid.